Perancangan Model Sistem Informasi Penunjang Operasional pada Lembaga Bimbingan Belajar - Oktavia, Tanty (ComTech: Computer, Mathematics and Engineering Applications, 2012)
Tutoring institution is an organization which classified in education which focuses on improving the quality of learning of all students in order to achieve the desired target. The operational activities on this institution consist of registration, scheduling, evaluation, and administration supporters. It will be less effective if the process is done manually. Therefore, many institutions are starting to restructure the model of information systems to support the company?s operations. This study describes about a design of information system model using object oriented approach introduced by Satzinger, which each phase is represented using UML diagrams. The result achieved in this research is to produce a general model of information systems in supporting the operations of a tutoring institution.